Physical activity and neurocognitive functioning in aging - a condensed updated review. Issue 1 (December 2016) - Gajewski, Patrick; Falkenstein, Michael
Abstract This condensed review gives an overview about two methodological approaches to study the impact of physical activity on cognition in elderly, namely cross-sectional studies and randomized controlled intervention studies with pre- and post-measures. Moreover, this review includes studies investigating different types of physical activity and their relation to cognitive functions in older age. Behavioral data are considered but the main focus lies on neuroscientific methods like event-related potentials (ERPs) and functional magnetic resonance imaging (fMRI).